Cathepsin S provokes interleukin-6 (IL-6) trans-signaling through cleavage of the IL-6 receptor in vitro - Flynn, Charlotte M.; Garbers, Yvonne; Düsterhöft, Stefan; Wichert, Rielana; Lokau, Juliane; Lehmann, Christian; Dudziak, Diana; Schröder, Bernd; Becker-Pauly, Christoph; Rose-John, Stefan; Aparicio-Siegmund, Samadhi; Garbers, Christoph (Scientific Reports, 2020)
The cytokine interleukin-6 (IL-6) fulfills its pleiotropic functions via different modes of signaling. Regenerative and anti-inflammatory activities are mediated via classic signaling, in which IL-6 binds to the membrane-bound IL-6 receptor (IL-6R). For IL-6 trans-signaling, which accounts for the pro-inflammatory properties of the cytokine, IL-6 activates its target cells via soluble forms of the IL-6R (sIL-6R). We have previously shown that the majority of sIL-6R in human serum originates from proteolytic cleavage and mapped the cleavage site of the IL-6R. The cleavage occurs between Pro-355 and Val-356, which is the same cleavage site that the metalloprotease ADAM17 uses in vitro. However, sIL-6R serum levels are unchanged in hypomorphic ADAM17ex/ex mice, making the involvement of ADAM17 questionable. In order to identify other proteases that could be relevant for sIL-6R generation in vivo, we perform a screening approach based on the known cleavage site. We identify several candidate proteases and characterize the cysteine protease cathepsin S (CTSS) in detail. We show that CTSS is able to cleave the IL-6R in vitro and that the released sIL-6R is biologically active and can induce IL-6 trans-signaling. However, CTSS does not use the Pro-355/Val-356 cleavage site, and sIL-6R serum levels are not altered in Ctss−/− mice. In conclusion, we identify a novel protease of the IL-6R that can induce IL-6 trans-signaling, but does not contribute to steady-state sIL-6R serum levels.
CRIS-Team Scopus Importer:2020-12-25